(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of 1-Methylcyclopropene (1-MCP) on quality andshelf–life of ‘Grand Nain’ banana fruits was evaluated.1-Methylcyclopropene at 62.5, 125 and 250 ppb delayed fruit ripening,maintained quality and extended shelf-life of banana fruits. The higher theconcentration of 1-MCP, the more was the effect. 1-Methylcyclopropenesignificantly delayed the onset of the climacteric peak. The untreatedfruits reached the climacteric peak after 8 days at 18± 1°C and 85% - 90%relative humidity. Treatment with 1-MCP at 62.5, 125 and 250 ppbsignificantly delayed the onset of the climacteric peak by 12, 16 and 20days, respectively, compared with the untreated fruits. The effect of 1-MCP was also reflected similarly in retarded peel colour development andtotal soluble solids (TSS) accumulation, reduced fruit flesh softening andweight loss, and retained ascorbic acid content during storage of bananafruits.